RHIIZOBACTERIA RESISTEN LOGAM BERAT ASAL TAMBANG EMAS PONGKOR INDONESIA DAN TAMBANG TEMBAGA MARINDUQUE FILIPINA - Erny Yuniarti; Ida F Dalmacio; Erlinda S Paterno (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2019)
The purposes of the study was to isolate, to characterize, and to identify rhizobacteria from plant rhizosphere growing in gold and copper mine. The isolation of rhizobacteria used N-free semisolid agar media, TSA, and SLP plus heavy metals (HMs), namely Pb, Cd, and or Cu. Isolated rhizobacteria were subsequently characterized for resistance to higher level of Pb, Cd, Cu in SLP media. Cultural and morphological characterization of rhizobacteria were conducted for cell morphology, motility, Gram staining, and biofilm formation. The rhizobacteria identification used sequence analysis of the 16S RNA gene fragments. The results showed that the majority of rhizobacterial from Cu mine site (66.7% of 21 isolates) were resistant to Cu (72150 ppm) while the majority of rhizobacteria from gold mine site (77.8% of 18 isolates) were sensitive to 72 ppm Cu. Majority of Cu in the soil was insoluble as granules attaching to gravel so that rhizobacteria of Cu mine site have been exposed and adapted to available Cu. This fact, explaining that the rhizobacteria’s MIC value was lower than the total Cu level in the soil. Three HMs-resistant rhizobacter (PbSM 2.1, MGR 334, and CuNFbM 4.1) formed biofilms, which was as one of the resistance mechanism to HMs. This research informed that HM contaminated-soil is better source for obtaining HM resistant rhizobacteria than HM uncontaminated-soil. The use four isolation media produce rhizobacteria which was more diverse than rhizobacteria from each isolation medium. Further characterization needs to be done to obtain HM resistant-rhizobacteria which can be used as biofertilizers and phytoremediation agent.